Potential of Ficus carica extracts against Euschistus heros: Toxicity of major active compounds and selectivity against beneficial insects. Issue 10 (28th June 2021) - Britto, Isabella O; Araújo, Sabrina H C; Toledo, Pedro F S; Lima, Graziela D A; Salustiano, Iorrana V; Alves, Janaína R; Mantilla‐Afanador, Javier G; Kohlhoff, Markus; Oliveira, Eugenio E; Leite, João Paulo V
Abstract: BACKGROUND: Using plant‐based extracts and their constituents has been suggested as an alternative tool to replace or integrate with the synthetic compounds used to manage insect pests. Here, we evaluated the potential of extracts obtained from Ficus carica Linn (Moraceae) branches and leaves against the Neotropical brown stink bug, Euschistus heros, one of the most prevalent insect pests in soybean fields. We further isolated and evaluated the toxicity of the extracts' major components against E. heros . Additionally, by using computational docking analysis and toxicological approaches, we assessed the physiological basis for the selectivity of these extracts against beneficial insects such as pollinator bees (i.e. Apis mellifera and the Neotropical stingless bee Partamona helleri ), ladybeetles ( Eriopis connexa and Coleomegilla maculata ), and lacewings ( Chrysoperla externa ). RESULTS: Our results demonstrate that branch (LC50 = 5.9 [4.7–7.1] mg mL –1 ) and leaf (LC50 = 14.1 [12.5–15.4] mg mL –1 ) extracts exhibited similar toxicity against E. heros . Our phytochemical analysis revealed psoralen and bergapten furanocoumarins as the major components of the extract. Based on our computational predictions, these molecules' differential abilities to physically interact with the acetylcholinesterases of E. heros and beneficial insects play relevant roles in their selectivity actions. The estimated LC90 values of branch (30.0 mg mL –1 ) and leaf (30.0 mg mL –1 ) extracts killed less than 12% of the beneficial insects. CONCLUSION: Overall, our findings revealed that furanocoumarin‐rich extracts obtained from F. carica extracts have the potential to be used as alternative tools in the integrated management of stink bug pests. © 2021 Society of Chemical Industry. Abstract : Extracts obtained from Ficus carica leaves and branches are rich in furanocoumarins (psoralen and bergapten) that selectively control Euschistus heros without affecting pollinator bees, ladybeetles, and lacewings.